Investigation of the hypothalamic defensive system in the mouse - Martinez, Raquel C. R.; Carvalho-Netto, Eduardo F.; Amaral, Vanessa C. S. [UNESP]; Nunes-de-Souza, Ricardo L. [UNESP]; Canteras, Newton S. (Elsevier B.V., 2008)
The hypothalamus plays especially important roles in various endocrine, autonomic, and behavioral responses that guarantee the survival of both the individual and the species. In the rat, a distinct hypothalamic defensive circuit has been defined as critical for integrating predatory threats, raising an important question as to whether this concept could be applied to other prey species. To start addressing this matter, in the present study, we investigated, in another prey species (the mouse), the pattern of hypothalamic Fos immunoreactivity in response to exposure to a predator (a rat, using the Rat Exposure Test). During rat exposure, mice remained concealed in the home chamber for a longer period of time and increased freezing and risk assessment activity. We were able to show that the mouse and the rat present a similar pattern of hypothalamic activation in response to a predator. of particular note, similar to what has been described for the rat, we observed in the mouse that predator exposure induces a striking activation in the elements of the medial hypothalamic defensive system, namely, the anterior hypothalamic nucleus, the dorsomedial part of the ventromedial hypothalamic nucleus and the dorsal premammillary nucleus. Moreover, as described for the rat, predator-exposed mice also presented increased Fos levels in the autonomic and parvicellular parts of the paraventricular hypothalamic nucleus, lateral preoptic area and subfornical region of the lateral hypothalamic area. In conclusion, the present data give further support to the concept that a specific hypothalamic defensive circuit should be preserved across different prey species. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: defensive behaviors; mouse; RET; anterior hypothalamic nucleus; ventromedial hypothalamic nucleus; dorsal premammillary nucleus